Nitrate place in modern cardiology - D. A. Zateyshchikov; E. N. Dankovtseva (Кардиоваскулярная терапия и профилактика, 2007)
The authors review therapeutic action mechanisms of nitrates and their use in cardiology practice. Nitrate effects are discussed, clinical data and modern recommendations on nitrate treatment in angina, acute myocardial infarction, heart failure, and arterial hypertension are presented. Nitrate tolerance mechanisms and their prevention are emphasized. Modern retard forms, isosorbide dinitrate, in particular, have some benefits, e.g., lower chances of tolerance development and withdrawal syndrome.